Antibiotic Use Among Hospitalized Children and Neonates in China: Results From Quarterly Point Prevalence Surveys in 2019 - Wang, Chu-ning; Tong, Jianning; Yi, Bin; Huttner, Benedikt D.; Cheng, Yibing; Li, Shuangjie; Wan, Chaomin; Zhu, Qingxiong; Zhou, Qionghua; Zhao, Shiyong; Zhuo, Zhiqiang; Wang, Daobin; et al. (Frontiers in Pharmacology, 2021)
Background Antimicrobial resistance is a significant clinical problem in pediatric practice in China. Surveillance of antibiotic use is one of the cornerstones to assess the quality of antibiotic use and plan and assess the impact of antibiotic stewardship interventions. Methods We carried out quarterly point prevalence surveys referring to WHO Methodology of Point Prevalence Survey in 16 Chinese general and children’s hospitals in 2019 to assess antibiotic use in pediatric inpatients based on the WHO AWaRe metrics and to detect potential problem areas. Data were retrieved via the hospital information systems on the second Monday of March, June, September and December. Antibiotic prescribing patterns were analyzed across and within diagnostic conditions and ward types according to WHO AWaRe metrics and Anatomical Therapeutic Chemical (ATC) Classification. Results A total of 22,327 hospitalized children were sampled, of which 14,757 (66.1%) were prescribed ≥1 antibiotic. Among the 3,936 sampled neonates (≤1 months), 59.2% (n=2,331) were prescribed ≥1 antibiotic. A high percentage of combination antibiotic therapy was observed in PICUs (78.5%), pediatric medical wards (68.1%) and surgical wards (65.2%). For hospitalized children prescribed ≥1 antibiotic, the most common diagnosis on admission were lower respiratory tract infections (43.2%, n=6,379). WHO Watch group antibiotics accounted for 70.4% of prescriptions (n=12,915). The most prescribed antibiotic ATC classes were third-generation cephalosporins (41.9%, n=7,679), followed by penicillins/β-lactamase inhibitors (16.1%, n=2,962), macrolides (12.1%, n=2,214) and carbapenems (7.7%, n=1,331). Conclusions Based on these data, overuse of broad-spectrum Watch group antibiotics is common in Chinese pediatric inpatients. Specific interventions in the context of the national antimicrobial stewardship framework should aim to reduce the use of Watch antibiotics and routine surveillance of antibiotic use using WHO AWaRe metrics should be implemented.